Gender differences in triple jump phase ratios and arm swing motion of international level athletes - Vassilios Panoutsakopoulos; Apostolos S. Theodorou; Dimitrios Katsavelis; Panagiotis Roxanas; Georgios Paradisis; Polyxeni Argeitaki (Palacký University Olomouc, 2016)
Background: Female triple jumping is a relatively new athletics event. A limited number of researchers have focused on comparing male and female jumpers competing in international events, resulting in scarce findings in the literature regarding gender differences of the determinants of triple jump performance. Objective: The aim of the study was to examine the possible gender differences in the approach step characteristics, the spatiotemporal parameters of the separate phases of the triple jump as performed by athletes participating in sub-elite international events. Methods: The male and female participants of the 2015 European Team Championships triple jump event were recorded with a panning video camera. Approach speed was measured using photocells. Kinematical parameters were extracted using the APAS WIZARD 13.3.0.3 software. The relationships between the examined parameters and the actual triple jump performance were examined with Pearson's correlation analysis. Repeated measures ANOVA and chi-square statistical tests were run to examine the significance of the differences between genders. Results: Approach speed significantly correlated with the actual jumping distance in both males and females (p < .05). Significant gender differences (p < .05) existed concerning basic kinematical parameters. Men were found to have larger average horizontal speed of the 11 m to 1 m segment of the final approach, step length of the final six steps of the approach, step frequency of the final two steps, actual phase distances and percentage distribution of the step. Women, unlike men, used solely single arm swing techniques. No athlete executed the jump using a jump dominated technique. Conclusions: Gender differences in triple jump performance lies upon the kinematical parameters of the final two steps of the approach, the length of the step phase and the support time for the jump. The technique elements of the penultimate step are suggested to be the factor for the existence of these differences.